1992
DOI: 10.1002/ajh.2830410102
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndromes and malignant solid tumors: Analysis of 21 cases

Abstract: We studied the association between myelodysplastic syndromes (MDS) and malignancies in a cohort of 155 patients with MDS, 21 of whom presented malignant solid tumors. Myelodysplasia was present after the diagnosis of cancer in eight patients (interval between the diagnosis of both conditions 18 months, median survival 49.5 months), simultaneously with diagnosis in 11 (median survival 8 months), and before malignancy in two patients (interval between the diagnosis of both conditions 47 and 7 months). One patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 15 publications
1
14
0
2
Order By: Relevance
“…Some authors suggested that the bone marrow myelodysplastic changes in association with solid tumors were paraneoplastic phenomena and not true MDS, since no cases developed acute leukemia [6]. Others, however, concluded that MDS conferred a much higher risk for developing solid tumors [21]. Despite their possible association with lymphoid neoplasia and solid tumors, primary MDS have virtually not been reported with HD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Some authors suggested that the bone marrow myelodysplastic changes in association with solid tumors were paraneoplastic phenomena and not true MDS, since no cases developed acute leukemia [6]. Others, however, concluded that MDS conferred a much higher risk for developing solid tumors [21]. Despite their possible association with lymphoid neoplasia and solid tumors, primary MDS have virtually not been reported with HD.…”
Section: Discussionmentioning
confidence: 97%
“…Although still debatable, MDS have been associated with the development of a variety of neoplasms other than acute myeloid leukemia (AML). Solid tumors such as carcinomas of lung, colon, prostate, and kidney have been reported at a higher incidence in association with MDS [21]. A similar association between MDS and lymphoid neoplasms such as acute lymphoblastic leukemia (ALL), non-Hodgkin's lymphoma (NHL), plasma cell neoplasms and chronic lymphocytic leukemia (CLL) has been reported [1,7,9,12].…”
Section: Introductionmentioning
confidence: 94%
“…Most of these malignancies were lymphoid neoplasms (chronic lymphocytic leukemia, 5 Hodgkin disease, 6 non-Hodgkin lymphoma of both B-cell and T-cell phenotypes, 7,8 multiple myeloma, 9 and monoclonal gammopathy) and a few were solid tumors (stomach, colon, lung, kidney, and prostate cancer). 10 Subtypes of MDS on the FAB classification varied: refractory anemia (RA), RA with ring sideroblast, RAEB, RAEB in transformation (RAEB-t), and chronic myelomonocytic leukemia. However, all of these previous cases were adults; to date, no pediatric cases have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of MDS (RARS type) and T cell lymphoblastic non-Hodgkin lymphoma has so far not been reported in the literature. The mechanisms responsible for the appearance of non-Hodgkin lymphoma in a patient with primary MDS are diverse: the neoplastic transformation of a common progenitor, the immunodeficiency induced by MDS and the consideration that MDS could be a paraneoplastic syndrome preceding therefore the development of lymphoproliferative disorders [5,6].…”
mentioning
confidence: 99%
“…The cytogenetic analysis confirmed the coexistence of these hematologic malignancies since the presence of the deletion of the long-arm of chromosome 20 (del 20q) has been linked to RA or RARS and the karyotypic abnormalities in chromosome 3 may be seen in non-Hodgkin lymphomas [1]. In the medical literature, few cases presenting a similar coexistence were reported, without performance of substantial cytogenetic confirmation, including any type of MDS (RA, RARS, RA with excess blasts, RA with excess blasts in transformation and chronic myelomonocytic leukemia) with a B or T cell non-Hodgkin lymphoma, with multiple myeloma and malignant solid tumors [2][3][4][5]. The coexistence of MDS (RARS type) and T cell lymphoblastic non-Hodgkin lymphoma has so far not been reported in the literature.…”
mentioning
confidence: 99%